Anticipatory Testimonies: Environmental Disaster in Claudine Jacques's Fictional Prophecies - Julia L Frengs (Studies in 20th & 21st Century Literature, 2015)
In Caledonian author Claudine Jacques's 2002 novel L'Âge du perroquet-banane, Parabole païenne, a tribal elder warns a man "from elsewhere": "in our country, if you remove a taboo bone, you disrupt the sea, if you touch it without respect you invite a cyclone, if you toss the bones of our elders you provoke a...tidal wave" (54). Although this work is set in a futuristic world after an ambiguous "Great Disaster" on an unnamed Oceanic island, the author manages to allegorically recount the history of the environmental atrocities attributed to the earth's human occupants that have transformed the present reality of the Oceanic region. This essay considers Claudine Jacques's L'Âge du perroquet-banane, Parabole païenne, as well as her novel Nouméa Mangrove (2010), as anticipatory testimonies. Both works of fiction call into question the very real violations of environmental human rights facing the diverse ethnic communities of the sui generis collectivity of New Caledonia: nuclear testing in the Pacific Ocean, pollution from the nickel mining industry, and the depletion of natural resources. This essay demonstrates how Jacques's works engage in environmentalism by bearing witness to and challenging environmental injustices in New Caledonia in particular, and on a broader scale, in the French-speaking Oceanic region.
Keywords: Claudine Jacques; New Caledonia; Oceania; Kanak; nickel; prophecy; testimony; environmentalism